Lexical neighborhood effects in pseudoword spelling - Tainturier, Marie-Josephe (Frontiers in Psychology, 2013)
The general aim of this study is to contribute to a better understanding of the cognitive processes that underpin skilled adult spelling. More specifically, it investigates the influence of lexical neighbours on pseudo-word spelling with the goal of providing a more detailed account of the interaction between lexical and sublexical sources of knowledge in spelling. In prior research examining this topic, subjects typically heard lists composed of both words and pseudo-words and had to make a lexical decision to each stimulus before writing the pseudo-words. However, these priming paradigms are susceptible to strategic influence and may therefore not give a clear picture of the processes normally engaged in spelling unfamiliar words. In our two Experiments involving 71 French speaking literature adults, only pseudo-words were presented which participants were simply requested to write to dictation using the first spelling that came to mind. Unbeknown to participants, pseudo-words varied according to whether they did or did not have a phonological word neighbour. Results revealed that low-probability phoneme/grapheme mappings (e.g., /o/ -> aud in French) were used significantly more often in spelling pseudo-words with a close phonological lexical neighbour with that spelling (e.g., /krepo/ derived from “crapaud”, /krapo/) than in spelling pseudo-words with no close neighbours (e.g., /frøpo/). In addition, the strength of this lexical influence increased with the lexical frequency of the word neighbours as well as with their degree of phonetic overlap with the pseudo-word targets. These results indicate that the activation from lexical and sublexical processes is integrated in the course of spelling, and a specific theoretical account as to how such integration may occur is introduced.